"This project is about me": the impact of gender and sexuality discrimination at school - Figueiredo, Renata Targino de; Santos, Cíntia Velasco; Azeredo, Renata Oliveira (The ESPecialist, 2025)
This article aims to investigate data generated from the accounts of female students and teachers from a public state school in Rio de Janeiro, gathered in a medium-length documentary produced by a group of 3rd grade high school students from the same school. The narratives are centered on the theme of gender discrimination and sexuality in the school context. The notions of identity, emotions and affections, in the different communicative situations reported, will be examined, using the theoretical basis of linguistic science and social psychology. The study considers the context of production and the effects of meanings constructed in language, analyzing the engaged stance of the group that produces the film, in the process of preparing and executing this collective project. We seek to understand the notion of collectividual, elaborated by Stetsenko (2013) in this critical social and pedagogical practice, within the framework of the Historical-Cultural Activity Theory (CHAT), initiated by Vygotsky (1930; 1934).